Factors associated with surface‐level caries incidence in children aged 9 to 13: the Iowa Fluoride Study. (26th July 2013) - Broffitt, Barbara; Levy, Steven M.; Warren, John; Cavanaugh, Joseph E.
Abstract Objective As dental caries can progress throughout a person's lifetime, understanding caries risk factors unique to specific life phases is important. This study aims to assess caries incidence and risk factors for young adolescents. Methods Participants in the longitudinal Iowa Fluoride Study were assessed for dental caries at approximately age 9 and again at age 13. These participants also filled out questionnaires concerning water sources, oral health habits, beverage intakes, parent education and family income. Caries progression (D2+F) was analyzed at the surface level. Mixed effects logistic regression was used to assess associations between surface‐specific first molar occlusal caries incidence and risk factors. Results Caries incidence was quite low except on the first molar occlusal surfaces. In initial models of specific risk factors, incidence was positively associated with the surface having a D1 lesion at baseline, low family income, having untreated decay or fillings on other teeth at baseline, lower home water fluoride level, and higher soda pop consumption. In the final multiple variable model, significant interactions were found between tooth brushing frequency and initial D1 status, and also between family income and home tap water fluoride level. Conclusions D2+F incidence on first molar occlusal surfaces in these young adolescents was associated with prior caries experience on other teeth as well as prior evidence of a D1 lesion on the occlusal surface. More frequent tooth brushing was protective of sound surfaces, and fluoride in home tap water was also protective, but significantly more so for adolescents in low‐income families.